2010
DOI: 10.1097/aog.0b013e3181f73fac
|View full text |Cite
|
Sign up to set email alerts
|

Postplacental or Delayed Insertion of the Levonorgestrel Intrauterine Device After Vaginal Delivery

Abstract: OBJECTIVE To estimate whether 6-month use of the levonorgestrel-releasing intrauterine device (IUD) would be higher when insertion occurred within 10 minutes of placental delivery compared with 6–8 weeks postpartum. METHODS We enrolled pregnant women planning vaginal deliveries and desiring a postpartum levonorgestrel-releasing IUD. Patients were randomly assigned when admitted in labor to postplacental or delayed IUD insertion. The women followed up in person at 6–8 weeks and 6 months and were contacted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(132 citation statements)
references
References 15 publications
9
120
1
2
Order By: Relevance
“…The four women who withdrew from the study had all been randomised to have LNG‐IUS inserted postpartum. This finding is similar to the findings from other studies that women are less likely to have LNG‐IUS inserted four to eight weeks postpartum than at the time of CS4 or vaginal delivery 5. It is plausible that women are less likely to attend to have LNG‐IUS inserted six weeks postpartum due to difficulty or inconvenience of accessing postpartum care, or fear of an outpatient procedure.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The four women who withdrew from the study had all been randomised to have LNG‐IUS inserted postpartum. This finding is similar to the findings from other studies that women are less likely to have LNG‐IUS inserted four to eight weeks postpartum than at the time of CS4 or vaginal delivery 5. It is plausible that women are less likely to attend to have LNG‐IUS inserted six weeks postpartum due to difficulty or inconvenience of accessing postpartum care, or fear of an outpatient procedure.…”
Section: Discussionsupporting
confidence: 87%
“…These advantages include convenience, high patient motivation and immediate contraception prior to resumption of ovulation 2, 3. Uptake may also be higher with insertion at the time of delivery, as two studies of LNG‐IUS insertion at the time of CS4 and vaginal delivery5 both found that the women in the delayed insertion group were less likely to have the device inserted. Another benefit of insertion at CS is that women who have LNG‐IUS inserted at CS also have less bleeding postpartum than women who have a copper‐containing intrauterine contraceptive device (IUCD) inserted or no IUCD inserted at the time of CS 6…”
Section: Introductionmentioning
confidence: 99%
“…36,37,55 Studies have shown that many women who desire an IUD at the time of delivery do not return for later insertion and that immediate insertion of IUDs provides similar contraceptive coverage as delayed insertion, even with higher expulsion rates with immediate insertion. 56,57 The emerging adolescent-specific data on IUDs are promising. However, there are some disadvantages.…”
Section: Iudsmentioning
confidence: 99%
“…69 The safety and tolerability of immediate postpartum placement of IUDs (within 10 minutes of delivery of the placenta) and postabortal placement of these devices have been demonstrated by numerous studies. 68,[70][71][72][73][74] Higher expulsion rates following postpartum placement have been observed following vaginal delivery, 47 but may be lower, at least short term, when IUDs are placed through the uterine incision at the time of elective cesarean delivery. 75,76 Utilization rates of IUDs at 6 and 12 months postpartum may be higher in those who have these methods placed immediately after delivery than those who have planned placement at their routine postpartum visit; and pregnancy rates are also lower among those who receive them promptly postpartum.…”
Section: Approaches To Reduce Rapid Repeat Pregnancies Among Adolescementioning
confidence: 99%
“…66,67 Short interpregnancy intervals are associated with a number of adverse pregnancy outcomes, such as intrauterine growth restriction and preeclampsia. 68 Contraceptive counseling should be administered throughout pregnancy rather than delaying the discussion until the postpartum visit. 69 The safety and tolerability of immediate postpartum placement of IUDs (within 10 minutes of delivery of the placenta) and postabortal placement of these devices have been demonstrated by numerous studies.…”
Section: Approaches To Reduce Rapid Repeat Pregnancies Among Adolescementioning
confidence: 99%